Wet Corn Stover Storage: Correlating Fiber Reactivity With Storage Acids Over a Wide Moisture Range - Essien, Dzidzor; Marshall, Megan N.; Richard, Tom L.; Ray, Allison (Frontiers in Energy Research, 2018)
Wet storage is synonymous with ensilage, a simple biotechnology that has been used to preserve forage for livestock feed for millennia. In this natural process, organic acids are produced by anaerobic microbial degradation of a small fraction of the biomass, and these acids reduce the pH to levels that minimize further microbial activity and can preserve the biomass for years as long as anaerobic conditions are maintained. These organic acids also result in mild pretreatment with potential to enhance downstream conversion processes, making this an effective storage strategy. However, the degree and significance of this natural pretreatment capability of ensiled storage on downstream processes has not previously been quantified across a range of storage conditions. In this study, the degree of pretreatment was investigated by measuring the reactivity of corn stover fiber to cellulolytic enzymes. Although the results indicated significant improvement in hydrolytic outcomes after wet storage, by a factor of up to 2.4, saccharification of cellulose to sugar monomers was still limited. The results also show that dominance of lactic acid in the ensilage process is key to wet storage [pretreatment] effectiveness as in the livestock feed industry. Lactic acid pKa value is lower than the pKa of other silage acids and lower than typical silage pH. This gives lactic acid the advantage of being in the more dissociated form, with more protons available to facilitate pretreatment hydrolysis. However, unlike the livestock feed industry, where quality feedstock is attainable within very narrow storage moisture range, for biofuel purposes, a wider range of 35 ―65% is appropriate in achieving a similar quality outcome. This is true both for the immediate fiber response to enzymes and with subsequent pretreatment. This wider moisture range implies more flexibility in harvest schedule without sacrificing feedstock quality, thus alleviating concerns over feedstock quality that biomass suppliers or biorefineries may have.